When faith meets choice: Brand awareness, trust, and consumer preferences toward Muhammadiyah products - Berkah, Dian; Hakim, M. Hanifuddin; Ridho Saputro, Andre; Bustami, Mohammad Reevany (al-Uqud : Journal of Islamic Economics, 2025)
Muhammadiyah, one of Indonesia’s largest Islamic organizations, is renowned for its contributions to religion, education, healthcare, social welfare, and the economy. Through its business entities, Muhammadiyah offers products and services grounded in Islamic values, catering to both its members and the broader public. In East Java’s increasingly competitive market, understanding the factors that shape consumer trust in Muhammadiyah’s products is essential. This study examines the impact of brand awareness, service quality, promotions, location, satisfaction, and pricing on consumer trust, and how trust, in turn, influences purchasing decisions. Using Structural Equation Modeling–Partial Least Squares (SEM-PLS), the results indicate that service quality, brand awareness, and location significantly affect consumer trust, with service quality emerging as the most influential factor. Notably, location exerts a negative effect, suggesting the presence of localized consumer perceptions. Consumer trust is found to significantly mediate purchasing decisions. The model demonstrates solid explanatory power, with R² values of 0.543 for trust and 0.293 for purchasing decisions, and a Goodness of Fit (GoF) score of 0.562. These findings imply that Muhammadiyah should prioritize enhancing service quality, bolstering brand awareness, and reevaluating its location strategies to strengthen consumer relationships and maintain market competitiveness.